Enhancing Intensive Listening Skills in Third-Grade Students: The Impact of YouTube Media: Memperkuat Keterampilan Mendengarkan Intensif pada Siswa Kelas III: Dampak Media YouTube - Namira, Aflakha Jihan; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aimed to investigate the effect of YouTube media on the intensive listening skills of third-grade students at SDN Cemeng Bakalan 2. A pre-experimental design with a One Group Pretest-Posttest research design was employed, using a saturated sample of 17 class III students. Data was collected through pretest and posttest evaluations of intensive listening skills. The results revealed a significant effect of YouTube media on the students' listening abilities, as demonstrated by the hypothesis test with a significance level of α = 0.05. With a p-value of 0.000 < 0.05, Ho was rejected, and Ha was accepted, indicating that learning using YouTube media resulted in noticeable improvements in the intensive listening skills of third-grade students. These findings hold implications for educators seeking innovative approaches to foster effective listening skills among young learners. Highlights: Significant Improvement: The study demonstrates a substantial enhancement in intensive listening skills among third-grade students through the use of YouTube media. Quantitative Research Approach: The research adopts a pre-experimental design method with a One Group Pretest-Posttest to measure the impact of YouTube media on student listening abilities. Innovative Educational Tool: YouTube media emerges as an effective and engaging tool to foster intensive listening skills, providing educators with a valuable resource to enhance learning outcomes. Keywords: Intensive Listening Skills, YouTube Media, Third Grade Students, Pre-Experimental Design, Educational Impact.